Prince William - Rand, Gloria; Rand, Ted (New York : H. Holt, 1992)
On Prince William Sound in Alaska, Denny rescues a baby seal hurt by an oil spill and watches it recover at a nearby animal hospital.
Elementary School Library Collection (Bro-Dart)
Publisher's Weekly
Booklist
4.8
K-3
Keywords: Seals (Animals) -- Fiction; Wildlife rescue -- Fiction; Oil spills -- Fiction; Pollution -- Fiction; Seals (Animals) -- Fiction; Wildlife rescue -- Fiction; Oil spills -- Fiction; Alaska -- Fiction; Alaska -- Fiction